Percutaneous kyphoplasty for a "centenarian": A case report and a summary of technical points. (August 2019) - Yang, Huilin; Ge, Jun; Liu, Hao; Zou, Jun
Abstract: Objective: To present a case of 97-year-old patient performed by Percutaneous kyphoplasty (PKP) with the key technology of diagnosis and therapy. Methods: To review literatures about super-aged patients suffering from osteoporotic vertebral compression fracture and summarize the treatment procedures and technical points. Results: The centenarian patient received a satisfied follow-up efficacy using the diagnosis and key technology of PKP. Conclusions: PKP is an effective surgical procedure for the treatment of super-aged patient using the diagnosis and key technology. Highlights: This work describes using Percutaneous kyphoplasty (PKP) for a "centenarian" for the very first time. Whereby, we discuss and summarize the technique points of PKP. This work summarize and discuss the treatment of vertebral compression fractures for super-aged patients.